Factors Influencing Competition in the Maize Milling Sector in South Africa - Mtisi, H. A.; Govender, K. K. (Richtmann Publishing, 2022)
Although the maize milling industry in South Africa is highly attractive and profitable, new entrants are unsuccessful. Thus, understanding the factors influencing competition is important for developing strategies which can help new entrants to be more resilient and also succeed. A case study of a very successful organization in the industry was conducted using Porters five forces model, to explore the factors influencing competition in the industry. The selected organization employs a differentiation strategy which enables it to constantly improve and introduce new maize meal varieties to serve a wide range of customers. The findings revealed that the selected organization employs resources, capabilities and knowledge in its business processes to sustain its competitive advantage. Thus, it is recommended that firms entering this industry should harmonize internal resources, knowledge, capabilities and external forces to generate a competitive advantage. Received: 18 November 2021 / Accepted: 30 December 2021 / Published: 5 January 2022